Analysis Of The Implementation Of Supplementary Feeding (PMPK) For Stunted Children In Kampar Regency, 2025 - Mas’udatul Isnaini; Mitra Mitra; Elfian Elfian (Jurnal Medika: Medika, 2026)
Stunting is a chronic nutrition problem that affects human resource quality and remains a national priority. One specific nutrition intervention implemented is the provision of Supplementary Feeding using Foods for Special Medical Purposes (PMPK). The success of this program depends on proper planning, implementation, and monitoring–evaluation systems. To analyze the implementation of PMPK activities for stunted children in the working area of the Kampar District Health Office in 2025. This residency used a qualitative descriptive design with a field study approach. Informants included nutrition program managers, health workers, and related stakeholders. Data were collected through in-depth interviews, observations, and document reviews. Thematic analysis was applied through data reduction, data display, and conclusion drawing. PMPK implementation in Kampar District generally follows national guidelines, covering planning, organizing, implementation, and monitoring–evaluation stages. However, several obstacles were identified, including limited human resources, varied understanding of PMPK among staff, and suboptimal recording and reporting systems. Fishbone analysis indicated that major problems originated from human, method, and system factors. PMPK implementation for stunted children in Kampar District has been conducted, but strengthening staff capacity, standardizing procedures, and improving monitoring and evaluation systems are necessary to enhance program effectiveness in reducing stunting